Project-based learning: One of a learning model to assess students’ creativity in processing local food - Baiq Fatmawati; H. Hunaepi (Research and Development in Education (RaDEn), 2025)
Local food processing enhances students' creativity and helps preserve and utilize local resources sustainably. The focus of this study is to determine students' ability to design and produce local food products through project-based learning. The research used validation studies that include preparing for the experiment, design experiment, and retrospective analysis. Respondents were 22 students in fourth semesters in the Biology Education Study Program, Faculty of Science and Mathematics, Hamzanwadi University. Data collection techniques using worksheets based project with indicators for design project: problem, solution, objective, procedure and product. Data analysis techniques using Gain product design assessment and Cohen's d test. The results of product planning for each group show medium and high categories, increasing creative thinking for each planning indicator, namely problems (0.7), solutions (0.8), objectives (0.7), tools and materials (1), and work methods (1). For the learning effects provided, based on the results of the Cohen's d test, project-based learning shows a large effect for all indicators in compiling environmental plans (1.8), solutions (2.6), objectives (1.6), tools and materials (2.6), and work methods (3.6). Based on the results of the product design gain and Cohen's d effect test, it can be concluded that students are able to design fermented products and project-based learning has a very good impact on the development of creativity and new concepts in processing local food into fermented food products that have useful tastes, shapes, and presentations.